Epistemic Duties and Failure to Understand one's Evidence - Scott Stapleford (Principia: An International Journal of Epistemology, 2012)
The paper defends the thesis that our epistemic duty is the duty to proportion our beliefs to the evidence we possess. An inclusive view of evidenced possessed is put forward on the grounds that it makes sense of our intuitions about when it is right to say that a person ought to believe some proposition P. A second thesis is that we have no epistemic duty to adopt any particular doxastic attitudes. The apparent tension between the two theses is resolved by applying the concept of duty to belief indirectly.